A BamHI family of highly repeated DNA sequences of Nicotiana tabacum - Koukalová, B; Reich, J; Matyášek, R; Kuhrová, V; Bezděk, M (TAG. Theoretical and applied genetics. Theoretische und angewandte Genetik, 1989)
HRS60.1, a monomer unit (184 bp) of a highly repeated nuclear DNA sequence of Nicotiana tabacum, has been cloned and sequenced. Following BamHI digestion of tobacco DNA, Southern hybridization with HRS60.1 revealed a ladder of hybridization bands corresponding to multiples of the basic monomer unit. If the tobacco DNA was digested with restriction endonucleases which have no target site in HRS60.1, the larger part of DNA homologous to HRS60.1 remained as uncleaved "relic" DNA. These results suggest a tandem arrangement of this DNA repeat unit. Four other clones of tobacco nuclear DNA cross-hybridized with HRS60.1, thus forming a "HRS60-family". Sequencing their inserts has shown their strong mutual homology. HRS60-family comprised about 2% of the nuclear genome of N. tabacum. Computer comparisons with other tandem plant-repeated DNA sequences could not detect any other homologous sequence.